Are Copper(I) Carbenes Capable Intermediates for Cyclopropanations? The Case for Ylide Intermediates. Issue 36 (14th July 2015) - Aldajaei, Jamal T.; Keeffe, James R.; Swift, Christopher A.; Gronert, Scott
Abstract A novel approach is used to synthesize a stable, ligated copper(I) carbene in the gas phase that is capable of typical metal carbenoid chemistry. However, it is shown that copper(I) carbenes generally undergo rapid unimolecular rearrangements including insertions into copper‐ligand bonds and Wolff rearrangements. The results indicate that most copper(I) carbenes are inherently unstable and would not be viable intermediates in condensed‐phase applications; an alternative intermediate that is less prone to rearrangements is required. Computational data suggest that ylides formed by the complexation of the carbene with solvent or other weak nucleophiles are viable intermediates in the reactions of copper(I) carbenes.